(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the efficiency of the teppanyaki production process for the Nishimura teppan beef steak set menu at Nishimura Restaurant, Shangri-La Hotel Surabaya, by reviewing three main indicators, namely material usage, production time, and labour. The study uses a quantitative descriptive approach supported by qualitative data. Data collection was conducted through direct observation of the production process, recording of raw material usage, measurement of time at each stage of production, and interviews with chefs and related parties. Quantitative data were analysed descriptively using material efficiency percentage calculations, while qualitative data were analysed through reduction and interpretation of work phenomena to reinforce quantitative findings. The results showed that material usage had reached an efficiency level with a yield percentage of 81% and waste of 19%, reflecting controlled raw material management in accordance with quality standards. In terms of time, all stages of pre-preparation and live cooking can be completed on time without disrupting service. Labour efficiency is demonstrated through the adaptive use of working time, characterised by minimal idle time. Overall, the teppanyaki production system is considered efficient and supports the smooth operation of the restaurant